On the structure of the Au18(SR)14 cluster - Tlahuice Flores, Alfredo; Garzón, Ignacio L. (Royal Society of Chemistry, 2012)
First principles calculations are used for a systematic search of the lowest-energy (most-stable) structure of the recently synthesized Au18(SR)14 cluster. A comparison of the calculated optical absorption and electronic circular dichroism spectra, which are highly sensitive to the cluster structure and chirality, with the experimental spectra of the glutathione-protected gold cluster, Au18(SG)14, is used to discriminate between low-energy isomers of the Au18(SR)14 (R = CH3) cluster. From the good agreement between calculated and measured spectra, it is predicted that the structure of the Au18(SR)14 cluster consists of a prolate Au8 core covered with two dimer (SR–Au–SR–Au–SR) and two trimer (SR–Au–SR–Au–SR–Au–SR) motifs. These results provide additional evidence on the existence of longer trimer motifs as protecting units of small thiolated gold clusters.